(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Renal biopsy is an indispensable tool for the accurate diagnosis and treatment of different forms of renal disease. Many advances have improved the utility and safety of renal biopsy procedure. Objective: To determine the extent to which renal biopsy used and how much it affects the Iraqi nephrology practice. Methods: A systematic review of articles published from 1990 to 2014 was carried out by searching Medline and Google scholar. We included all studies that concerned with renal biopsy as the main intervention. Eligible studies determined by predefined criteria were reviewed. Data from these studies combined and analyzed. Results: The search yielded 55 title, of which, eleven studies met the inclusion criteria. Analysis of the 11 studies (2278 patients) that underwent 2667 renal biopsies. Ten studies centered on native renal pathology and one study focused on allograft pathology. Conclusion: The Iraqi renal biopsy practice and pathology interpretation need to be rejuvenated by modern pathology services, data registry, and well-designed studies with clinical impact. Keywords: Renal biopsy, Allograft, Pathology, Iraq. DOI: 10.22578/IJMS.14.4.13